2002
DOI: 10.1016/s0038-1098(02)00432-5
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental optical absorption of CsPbI3 and Cs4PbI6

Abstract: The fundamental optical absorption spectra of CsPbI3 and Cs4PbI6 have been measured for the first time. There are distinct differences in the absorption characteristic between the two compounds: Cs4PbI6 exhibits strong, oscillator-like absorption and a prominent, blue-shifted excitonic peak, compared to the case of CsPbI3. The differences are explainable in terms of whether the Pb2+(I-)6 octahedra are weakly (CsPbI3) or strongly (Cs4PbI6) mutually isolated in the respective compounds

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
45
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 13 publications
3
45
0
3
Order By: Relevance
“…Смесь порошков предварительно расплавлялась под экраном, помещенным между испа-рителем и подложкой, затем расплав испарялся на под-ложку. Температуру подложки варьировали от 373 до 403 К. При температуре подложки T sub = 393 К полу-чаются монофазные пленки RbPbI 3 с характерным для этого соединения спектром, подобным спектру CsPbI 3 [7][8][9], с интенсивной длинноволновой А I -полосой при 2,975 эВ (90 К) на краю поглощения. В спектре тонких пленок, полученных при более низкой температуре подложки T sub ≈ 353 К, кроме А I -полосы, присущей RbPbI 3 , появляется более высокочастотная А II -полоса, соответствующая, по-видимому, второму тройному со-единению (рис.…”
Section: экспериментunclassified
See 2 more Smart Citations
“…Смесь порошков предварительно расплавлялась под экраном, помещенным между испа-рителем и подложкой, затем расплав испарялся на под-ложку. Температуру подложки варьировали от 373 до 403 К. При температуре подложки T sub = 393 К полу-чаются монофазные пленки RbPbI 3 с характерным для этого соединения спектром, подобным спектру CsPbI 3 [7][8][9], с интенсивной длинноволновой А I -полосой при 2,975 эВ (90 К) на краю поглощения. В спектре тонких пленок, полученных при более низкой температуре подложки T sub ≈ 353 К, кроме А I -полосы, присущей RbPbI 3 , появляется более высокочастотная А II -полоса, соответствующая, по-видимому, второму тройному со-единению (рис.…”
Section: экспериментunclassified
“…1, кривая 1). Аналогичная ситуация на-блюдалась для соединений системы CsI-PbI 2 [6][7][8][9], в которой при низких температурах подложки (T sub ≤ ≤ 353 К) получались двухфазные пленки (рис. 1, кри-вая 3), которые после отжига в течение несколь-ких часов при температуре свыше 400 К переходили в монофазные со спектром, характерным для Cs 4 PbI 6 (рис.…”
Section: экспериментunclassified
See 1 more Smart Citation
“…This band was attributed to the Cs 4 PbI 6 compound in [9], and it was concluded that CsPbI 3 is unstable in the gas phase and decomposes to form Cs 4 PbI 6 . The results of [7,9] encouraged Japa nese physicists [10,11] to develop methods for prepar ing pure CsPbI 3 and Cs 4 PbI 6 phases to measure their absorption spectra. Kondo et al [10,11] proposed to deposit successively thin CsI and PbI 2 layers of a cer tain thickness on a transparent substrate cooled to 77 K. The ratio of the thicknesses of the two layers was chosen according to the molar composition of the desired compound.…”
mentioning
confidence: 99%
“…4 (from [46]), where a sequence of solid-state chemical reaction is monitored by in-situ absorption spectroscopy for a film-crystal interface of a PbI 2 /CsI system (PbI 2 film on (0 0 1) CsI substrate). Annealings at the different temperatures indicated of a starting amorphous PbI 2 film, quench deposited onto a (0 0 1) CsI substrate cooled to 77 K, yield crystallites of PbI 2 (290 K), CsPbI 3 (400 K) and Cs 4 PbI 6 (480 K), respectively.…”
mentioning
confidence: 99%